Comparison of endoscopic ultrasound-guided fine-needle biopsy versus fine-needle aspiration for genomic profiling and DNA yield in pancreatic cancer: a randomized crossover trial - Kandel, Pujan; Nassar, Aziza; Gomez, Victoria; Raimondo, Massimo; Woodward, Timothy A.; Crook, Julia E.; Fares, Natalie S.; Wallace, Michael B. (Endoscopy, 2020)
Background National guidelines recommend genomic profiling of tumor tissue to guide precision therapy. We compared the specimen adequacy for genomic profiling and yield of DNA between endoscopic ultrasound (EUS)-guided fine-needle biopsy (FNB) and EUS-guided fine-needle aspiration (FNA).Methods In our tandem, randomized controlled trial, consecutive patients undergoing EUS for evaluation of pancreatic masses underwent both conventional EUS-FNA with a 25-gauge needle and paired EUS-FNB (19 or 22-gauge needle), with the order randomized (EUS-FNA first followed by EUS-FNB, or vice versa). A minimum of one pass with each needle was obtained for histology. Second and third passes were performed to collect DNA. Specimens were evaluated by a cytopathologist blinded to the needle type. Specimen adequacy for genomic profiling was calculated based on FoundationOne clinical diagnostic (CDx) adequacy requirements. We compared the adequacy for genomic profiling DNA (quantity) and histology yields with both needles.Results Analysis included 50 patients (25 men; mean age 68 [standard deviation (SD) 13] years), with a mean lesion size of 38 (SD 17) mm; 37 lesions (74 %) were pancreatic ductal adenocarcinoma (PDAC). The mean DNA concentrations in PDAC by FNB and FNA needles were 5.930 (SD 0.881) µg/mL vs. 3.365 (SD 0.788) µg/mL, respectively (P = 0.01). The median standardized histology score per pass with EUS-FNB was 5 (sufficient for histology) and for EUS-FNA was 2 (enough for cytology). Specimen adequacy for genomic profiling and yield of DNA was significantly higher with FNB than with FNA needles.Conclusions In this study, adequacy for genomic profiling, DNA, and histology yield were considerably superior using an EUS-FNB needle compared with an EUS-FNA needle.